Long noncoding RNA LISPR1 is required for S1P signaling and endothelial cell function. (March 2018) - Josipovic, Ivana; Pflüger, Beatrice; Fork, Christian; Vasconez, Andrea E.; Oo, James A.; Hitzel, Juliane; Seredinski, Sandra; Gamen, Elisabetta; Heringdorf, Dagmar Meyer zu; Chen, Wei; Looso, Mario; Pullamsetti, Soni Savai; et al.
Abstract: Sphingosine-1-Phosphate (S1P) is a potent signaling lipid. The effects of S1P are mediated by the five S1P receptors (S1PR). In the endothelium S1PR1 is the predominant receptor and thus S1PR1 abundance limits S1P signaling. Recently, lncRNAs were identified as a novel class of molecules regulating gene expression. Interestingly, the lncRNA NONHSAT004848 (LISPR1, Longi ntergenic noncoding RNA antisense toS 1PR1 ), is closely positioned to the S1P1 receptors gene and in part shares its promoter region. We hypothesize that LISPR1 controls endothelial S1PR1 expression and thus S1P-induced signaling in endothelial cells. In vitro transcription and translation as well as coding potential assessment showed that LISPR1 is indeed noncoding. LISPR1 was localized in both cytoplasm and nucleus and harbored a PolyA tail at the 3'end. In human umbilical vein endothelial cells, as well as human lung tissue, qRT-PCR and RNA-Seq revealed high expression of LISPR1. S1PR1 and LISPR1 were downregulated in human pulmonary diseases such as COPD. LISPR1 but also S1PR1 were induced by inflammation, shear stress and statins. Knockdown of LISPR1 attenuated endothelial S1P-induced migration and spheroid outgrowth of endothelial cells. LISPR1 knockdown decreased S1PR1 expression, which was paralleled by an increase of the binding of the transcriptional repressor ZNF354C to the S1PR1 promoter and a reduction of the recruitment of RNA Polymerase II to the S1PR1 5'end. This resulted in attenuated S1PR1 expression and attenuated S1P downstream signaling. Collectively, the disease relevant lncRNA LISPR1 acts as a novel regulatory unit important for S1PR1 expression and endothelial cell function. Highlights: LISPR1 and S1PR1 are highly expressed in endothelial cells and reduced in COPD. LISPR1 is important for migration and sprouting of endothelial cells. S1PR1 gene expression requires LISPR1 for RNA Pol II recruitment to S1PR1 5'UTR. LISPR1 may block transcriptional repressor ZNF354C binding to S1PR1 promoter. LISPR1 controls S1P targets ICAM1, PECAM1 and ANGPT2 through S1PR1.